Potential of Solid Wall Panel Implementation for Enhancing Construction Practices in Affordable Housing Projects - Abd Hamid, Siti Nur Liyana; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2024)
Affordable housing is one of the needs of people nowadays. Particularly in big cities, the housing market has seen a rise in property prices. The purpose of the study is to seek the potential of solid wall panel implementation for enhancing construction practices in affordable housing projects. Therefore, the objectives of the study are to investigate the potential, effectiveness, and improvement suggestions for solid wall panel implementation in affordable housing projects. To achieve the objectives, this research was conducted using qualitative methods for primary data collection and literature review by gathering information from books, journals, and proceedings, as secondary data. In addition, semi-structured interviews were conducted with G5 and G7 contractors, manufacturers, and developers of solid wall panels and the focus spots were in Selangor, Johor, Kuala Lumpur, and Melaka which are IBS expertise. Furthermore, the data was analysed using content analysis to provide data information related to the project. The significant findings from this study provide the potential of solid wall panel implementation, as key criteria to investigate, analyse and develop solutions, also propose and improve the implementation. In conclusion, this research contributes to a better understanding of the potential of solid wall panels as they can be implemented in construction practices in affordable housing.